PENERJEMAHAN KOSA KATA BUDAYA INDONESIA DALAM RUBRIK LIFE LINES DI HARIAN THE JAKARTA POST - Hardiyanti, Diana; Ocktarani, Yesika Maya (Universitas Muhammadiyah Semarang, 2014)
This study attempts to figure out the existing and interesting relationship between translation and culture. How the Indonesian cultural words were translated and explained to the reader of the English newspaper. The aims of this study are to define the cultural words in Life Lines rubric from The Jakarta Post Newspaper, how they were explained to the target language reader using translation method, what strategies being used and whether the results in the target language are considered equivalent. This study uses a qualitative descriptive method. The data for this study are Indonesian cultural words found in article. The data were taken from the Life Lines rubric published from March until May 2014. The Rubric is about the social life of the society, sometimes it writes about society, culture and life. The data consists of Indonesian cultural words as the source language and their explanation in English as the target language.The finding shows that from 58 articles of the rubric published within 3 months, there are 76 cultural words found in the article. From 76 data, 36 words are categorized into material culture, 13 words into social culture, 2 words into ecology, 25 words into organization etc. The translation strategies are loan words, loan words plus explanation, paraphrase, and illustration.The translation in the target language shows that 72 data are equivalent to the source language, 3 data are less equivalent, and 1 data is not equivalent to the source language.